SUPPLY CHAIN RISK MANAGEMENT DAN ANALISIS STRUKTUR BIAYA LOGISTIK UNTUK MITIGASI DAMPAK NEGATIF MIKOTOKSIN PADA KOMODITAS JAGUNG (Zea Mays L) - , MEGITA RYANJANI TANUPUTRI, Dr. Ir. Adi Djoko Guritno, M.SIE. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Corn (Zea mays L.) is a susceptible agricultural commodity by mycotoxins contamination and it possibly causes negative effects on food safety. Environmental conditions throughout the supply chain as a key trigger of mycotoxins growth can be identified visually. The objectives of this study are to identify the factors triggering the growth of mycotoxins, analyze the cost structure of logistics, and mitigate the potential risks associated with logistics costs to reduce the mycotoxins. This research was conducted by convenience sampling method and in-depth interview to the respondents throughout the supply chain. Locations of this study were done in central of corn production in Central Java and Yogyakarta province, Indonesia. Risk analysis method using the ISO 31000:2009 standard and logistics cost structure analysis using Activity-Based Costing. The results show that the emergences of mycotoxins were identified at each stage of the supply chain. In farmers level, there are 4 activities in the avoid risk category and in the level of the collectors and traders respectively consist of 3 activities. Risk mitigation at the farmers level is proposed through the involvement of technology in the improvement of pre-harvest handling, while at the collectors and traders level can be done through the lead time reduction and water content control below 17% wet basis in inventory. Analysis of logistics cost structure shows that the dominant logistics cost is identified in the material handling, transportation and inventory activities that contribute to 66.66%, 16.08% and 8.97% of the total logistics cost. Combination of avoid risk category and logistics costs along supply chain proposed recommendation to improve material handling and inventory activities. This research concludes that there is a linkage between the structure of logistics costs and preventive activities to prevent mycotoxins growth happens along the supply chain. Keywords: corn, supply chain, mycotoxins, risk management, logistics costs